The effectiveness of special development institutions for child perpetrators of immoral crimes - Syahputra, Aryo (Estudiante Law Journal, 2025)
This study aims to find out what factors are behind children becoming perpetrators of immoral crimes and what is the pattern of special child development institutions that commit immoral crimes in Gorontalo. The type of research used is the Emperis type of research with a Case approach. The results of this study show that the factors that cause children to be involved in becoming perpetrators of asusisla crimes are: (1) Factors of lack of education from parents, (2) Factors of perpetrators who have sexual disorders and minors who are already dating people who are much more mature, (3) economic factors, (4) educational factors, (5) environmental factors. Effectiveness of the Pattern of Special Development Institutions for Children Who Commit Immoral Crimes in Gorontalo using the System: (1) Inputs, (2) Processes,